2023
DOI: 10.1057/s41599-023-01750-7
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for metaverse governance based on technical standards

Abstract: Technical standards in digital technology can now be utilised to gather numerous digital sub-universes into the metaverse. However, how to create and implement guidance for the metaverse based on technical standards remains unexplored. This study investigated the theoretical framework and policy implications for future technical standards-based metaverse governance (TS-MG). The methodology entailed reviewing the available metaverse governance literature to establish both theoretical and case analyses of practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Drawing on interdisciplinary research into the ethical, psychological, and safety implications of virtual interactions, this study seeks to find a balance among user rights, platform accountability, and the demands of technological advancement. It also considers how cyberlaw precedents addressing issues like cyberbullying and cyberstalking could influence Metaverse-specific regulations (L. Yang 2023). A comprehensive framework, informed by comparative legal analysis and multidisciplinary insights, was developed to address the unique challenges of sexual violence in virtual environments.…”
Section: Framework Developmentmentioning
confidence: 99%
“…Drawing on interdisciplinary research into the ethical, psychological, and safety implications of virtual interactions, this study seeks to find a balance among user rights, platform accountability, and the demands of technological advancement. It also considers how cyberlaw precedents addressing issues like cyberbullying and cyberstalking could influence Metaverse-specific regulations (L. Yang 2023). A comprehensive framework, informed by comparative legal analysis and multidisciplinary insights, was developed to address the unique challenges of sexual violence in virtual environments.…”
Section: Framework Developmentmentioning
confidence: 99%
“…However, the implementation of the metaverse involves different governance modes. Technical standards in governance need to distinguish various stakeholders, such as government departments, industrial alliances, enterprises and consumers (Yang, 2023). Chen, Gun, Wu, Lin, & Chen (2024) suggested that the combination between the metaverse and smart cities can improve the quality of life of citizens and enable more efficient governance and management systems.…”
Section: The Irruption Of the Metaverse In The Management Of Tourism ...mentioning
confidence: 99%
“…Researchers in Bai et al (2023), Bale et al (2022), Barta et al (2023), Bibri and Allam (2022), Brown et al (2020), Brusamento et al (2019), Buck and McDonnell (2022), Chávez et al (2020), Chen et al (2020), Clus et al (2018), Di Pietro and Cresci (2021), Dube and İnce (2019), Dyer et al (2022), Falchuk et al (2018), Far and Rad (2022), Gannotta et al (2018), Hine (2023), Hyun (2021), Jeon and Jung (2021), Kaddoura and Al Husseiny (2023), Kim et al (2022), Kyaw et al (2019), Lin et al (2022), Liu, Rui, et al (2021), López‐Ojeda and Hurley (2023), Mystakidis (2022), Na et al (2022), Rejeb et al (2023), Said (2023), Satava and Jones (2003), Soriani and Bonafede (2023), Vladimirov et al (2022), Wang et al (2022), Yang (2023), Yang et al (2022), and Zhao et al (2022) discussed advantages, disadvantages, potential threats, ethical consideration, security, privacy, technologies, and future directions of the “metaverse”. Some researchers covered the metaverse subject of the most modern technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Governments can now organize virtual town hall meetings and solicit public feedback on policy because of the metaverse, which creates new avenues for citizen interaction. Studies in Barta et al (2023), Bibri and Allam (2022), Lombart et al (2020), Peukert et al (2019), Pizzi et al (2019), Van Kerrebroeck et al (2017), and Yang (2023) engaged with business, governance, and city services‐related research.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation